Birth during on-call period: Impact of care organization on mortality and morbidity of very premature neonates - Cambonie, Gilles; Theret, Bénédicte; Badr, Maliha; Fournier, Patricia; Combes, Clémentine; Picaud, Jean-Charles; Gavotto, Arthur (Frontiers in Pediatrics, 2022)
Objectives: The evidence that risks of morbidity and mortality are higher when very premature newborns are born during the on-call period is inconsistent. This study aimed to assess the impact of this situation among other determinants of outcomes, particularly newborn characteristics and care organization. Methods: Observational study including all infants born <30 weeks’ gestation in a French tertiary perinatal center between 2007 and 2020. On-call period corresponded to weekdays between 6:30 p.m. and 8:30 a.m., weekends, and public holidays. The primary endpoint was survival without severe morbidity, including grade 3-4 intraventricular hemorrhage (IVH), cystic periventricular leukomalacia, necrotizing enterocolitis, severe bronchopulmonary dysplasia (BPD); and severe retinopathy of prematurity. The relationship between admission and outcome was assessed by an adjusted odds ratio (aOR) on the propensity of being born during on-call period and expressed vs weekday. Secondary analyses were carried out in extremely preterm newborns (<27 weeks’ gestation), in cases of early death (within 7 days), and before (2007-2013, 51.5% of the cohort) vs after (2014-2020, 48.5% of the cohort) the implementation of a pediatrician-nurse team dedicated to newborn care in the delivery room. Results: 1064 infants [27.9 (26.3; 28.9) weeks, 947 (760; 1147) g] were included: 668 during the on-call period (63%) and 396 (37%) on weekdays. For infants born on weekdays, survival without severe morbidity was 54.5% and mortality 19.2%. During on-call, these rates were 57.3% [aOR 1.08 (0.84-1.40)] and 18.4% [aOR 0.93 (0.67-1.29)]. Comparable rates of survival without severe morbidity [aOR 1.42 (0.87-2.34)] or mortality [aOR 0.76 (0.47-1.22)] were observed in extremely preterm infants. The early death rate was 6.4% on weekdays vs 8.2% during on-call [aOR 1.44 (0.84-2.48)]. Implementation of the dedicated team was associated with decreased rates of mortality [aOR 0.57 (0.38, 0.85)] and grade 3-4 IVH [aOR 0.48 (0.30, 0.75)], and an increased rate of severe BPD [aOR 2.16 (1.37, 3.41)], for infants born during on-call. Conclusions: In this cohort, most births of very premature neonates occurred during the on-call period. A team dedicated to newborn care in the delivery room may have a favorable effect on the outcome of infants born in this situation.